The initial secondary school teacher education: perceptions of students in practices - Arroyo Salgueira, Sandra; Iglesias Martínez, Marcos Jesús; Lozano Cabezas, Inés (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The initial teacher education requires observing and reflecting on the educational reality, basing the theory on classroom practice, and developing skills that enable professional performance. The purpose of this paper is analyse the perceptions of future teachers, from the Master of Secondary Education, Baccalaureate and Vocational Training, about the quality of the training received in this period. The results show difficulties in their relationship with the students of the practice centres and lack of resources to develop didactic programs. As proposals for improvement, they request classes with constructivist approaches that bring theory and practice closer together and increase educational quality.